Development of Islamic Educational Institutions in Increasing Competitiveness in Madrasah Tsanawiyah - Rosyadi, Imron; Aprilianto, Andika; Rofiq, Muhammad Husnur; Bisri, Abdul Mukti; Sururi (Chalim Journal of Teaching and Learning, 2023)
Description of the subject's behavior processes according to the focus of the problem under study. The technique of collecting data uses observation, interviews, and documentation. The data used are primary and secondary data. To check the validity of the data using the triangulation method. The data analysis technique uses descriptive techniques with four steps, namely: (1) data collection or data collection (2) data reduction or data reduction (3) display data or data presentation (4) conclusion. The results showed that currently the MTs. Al-Hasanuddin of Pasuruan City, the concept of school development in improving competitiveness is in accordance with the concept of vision, mission, and objectives, quality of learning in accordance with the national curriculum, outstanding students both academically and non-academically An Nashr in understanding the Qur'an, improving facilities and infrastructure with stakeholder participation. The implementation of a curriculum administration strategy that is good for improving the quality of human resources (teachers and students), implementing discipline of teachers and students, establishing good relations with local communities, involving local communities in school activities, then improving quality with 14 steps according to Crosby, and Implications in this study in the form of customer satisfaction, a climate that is conducive, pleasant, orderly and quality in accordance with the expectations of the community so that it can attract market attention (community) to send their children to school at Al-Hasanuddin Junior High School, Pasuruan City.